Different Look, Same Blood: The Portrayal of Vampire in The Twilight Saga and The Little Vampire - Muushanaatin, Faaza; Alfiani, Fitria Arum; Janah, Nuur Laelatul; Saputri, Dian; Putri, Annissa Faradea Melliana; Tamami, Nabila Huwaida Asy syfa; Lirisworo, Lathifah (Pendidikan Bahasa dan Sastra Universitas Muhammadiyah Purworejo, 2025)
This research discussed the differences in the portrayal of vampires in The Twilight Saga and The Little Vampire by using the theory of atavism by Leeder (2013) and the theory of ameliorative by Mathews (2013). The purpose of this research was to analyse how vampire characters were designed to suit different age target audiences, namely children and young adults. This research used a qualitative research approach and Spradley's data analysis technique to process visual and textual data from the films. The results showed that in The Twilight Saga, vampires were portrayed as more ameliorative, with humane and emotional traits that were more suitable for adult audiences. In contrast, vampires in The Little Vampire tended to be more atavistic, with primitive traits delivered with elements of humour, which were more suitable for children audiences. The differences between the two films show how the representation of vampires was adapted to different target audiences. This research not only showed the differences in vampire portrayals, but also opened up opportunities for researchers who wanted to study supernatural creatures in modern culture.